The effectiveness of the bilobed pectoralis major myocutaneous flap at a tertiary care hospital: A retrospective analytical study - Rohit Kumar Jha (Wolters Kluwer Medknow Publications, 2021)
Background: Cosmetic defects after the major orofacial disease corrections may have an effect on the overall well-being of the patient. Head-and-neck cosmetic surgeries after a major episode of oral cancer impact the functional ability of the individual in several ways. In general, two types of flap are used in reconstructive surgery: microvascular free flaps and regional pedicle flaps. In socioeconomically poor countries like India, bilobed pectoralis major myocutaneous (PMMC) flap has been seen as a mainstay in facial reconstructive surgeries. Materials and Methods: The present study was conducted on 100 individuals with oral neoplasm who underwent resective surgery had a soft-tissue defect. All the complications that arose after reconstructive surgery were noted. Simple proportions were recorded. Results: Majority of the individuals had the buccal mucosa as the common site of oral neoplasm, and the tumor nodes and metastases staging was I + II. One individual sustained total flap necrosis. Wound infection and dehiscence were the most common complications. Conclusions: PMMC is best proven for flap reconstruction in oral neoplasm cases. It is established to be effective with good acceptability and very few complications. Due to these reasons, in spite of the known advances in facial reconstructive surgeries, this technique is widely followed in developing countries.